Intermediate Jacobians and the slice filtration - Park, Doosung (MATHEMATICA SCANDINAVICA, 2022)
For every n-dimensional smooth projective variety X over ℂ, the motive M(X) is expected to admit a Chow-Künneth decomposition M_0(X)… M_2n(X). Inspired by the slice filtration of M(X) we propose the definitions of M_2(X) and M_2n-2(X). In our construction we use intermediate Jacobians.